THE SYSTEM OF POWER CONSUMING MONITORING AND MANAGEMENT - Voloshyn, S.M. (Енергетика і автоматика, 2016)
The description of a system of monitoring and managing power consuming of an object is given. The system enables effective administration of power consuming systems that, in its turn, decreases the expenditures on energy.